Peranan Pengawasan Dinas Perhubungan Kabupaten Bekasi terhadap Parkir Ilegal di Lingkungan Minimarket - Muhamad Kelvin Aditya; Akbar Sayudi (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the implementation, effectiveness, and optimization strategies of supervision by the Bekasi Regency Transportation Department over illegal parking at convenience stores, which number 642 units across 23 sub-districts. It employs an empirical method with a qualitative approach through interviews, observation, and documentary study. The findings show that supervision in its preventive, repressive, and corrective dimensions has not run optimally due to the absence of a standard operating procedure, outreach, inspections, sanctions, and inter-agency coordination, compounded by ambiguity over authority regarding the semi-public status of store parking areas and a regulatory gap in Bekasi Regent Regulation Number 103 of 2016. Based on Soerjono Soekanto's five factors of legal effectiveness, the supervision is considered ineffective due to weak legal substance, inadequate facilities such as a digital data system, low legal awareness among the public and store managers, and a passive, permissive legal culture. The recommended optimization strategy includes accelerating regulation of semi-public land, applying graduated administrative sanctions, strengthening inter-agency coordination, utilizing information technology, formalizing parking attendants, and strengthening the Transportation Department institutionally.